Genetically Modified Mosquitoes - Eric P. Caragata; Yoosook Lee; Eva A. Buckner (EDIS)
Genetically modified (GM) mosquitoes are controversial, partly because of misinformation. This publication provides science-based information about GM mosquitoes to the public and anyone involved in mosquito control. It explains what GM mosquitoes are and why they are being investigated as a tool for mosquito control. Describes a GM mosquito pilot project in Florida, and includes FAQs and answers explaining how GM mosquitoes are created and their potential impacts on people and the environment.